INOVASI PENERAPAN BISNIS PRODUK PINTU PANEL BERBASIS BAHAN BAKU BATANG KELAPA SAWIT SISA KEGIATAN REPLANTING - Fakhri; Haji Gussyafri; Azhari; Elianora; Lisa Suryani; Hendro Ekwarso; Zulkifli Nurdin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract Replanting activities on oil palm land will leave solid waste of oil palm trunks. Efforts to utilize it will provide a solution to reduce the impact of environmental pollution, as a business opportunity for business units in the wood sector, and can be an alternative material to replace commercial wood. However, the implementation of a business based on palm oil stem raw materials still requires assistance in the timber industry. The aim of the activity is to provide business innovation solutions for the use of palm oil trunk waste as raw material for panel door products in wood processing business units. The problem-solving method is carried out by providing skills training to timber industry partners in the Tapung District, Kampar Regency and Pekanbaru City. The results of the activity have been able to provide partners with technical understanding and calculation of the economic value of panel door production from palm oil stem raw materials. Technically and economically implementing the business of utilizing oil palm trunks can compete with other commercial wood panel door materials, and can provide business opportunities for the timber industry unit in the future. Abstrak Kegiatan replanting pada lahan sawit akan menyisakan limbah padat batang kelapa sawit. Upaya pemanfaatannya akan memberikan solusi untuk mengurangi dampak pencemaran lingkungan, sebagai peluang bisnis bagi unit usaha di bidang perkayuan, serta dapat menjadi bahan alternatif pengganti kayu komersial. Namun, penerapan bisnis berbasis bahan baku batang kelapa sawit masih perlu pendampingan pada industri perkayuan. Tujuan kegiatan adalah untuk memberikan solusi inovasi bisnis terhadap pemanfaatan limbah batang sawit sebagai bahan baku produk pintu panel di unit-unit usaha pengolahan kayu. Metode pemecahan masalah dilakukan dengan cara memberikan pelatihan keterampilan pada mitra industri perkayuan di wilayah Kecamatan Tapung, Kabupaten Kampar dan Kota Pekanbaru. Hasil kegiatan telah dapat memberikan pemahaman teknis dan perhitungan nilai ekonomis produksi pintu panel dari bahan baku batang kelapa sawit pada mitra. Penerapan bisnis pemanfaatan batang kelapa sawit secara teknis dan ekonomis dapat bersaing dengan bahan pintu panel dari kayu komersial lainnya, serta dapat memberikan peluang bisnis bagi unit industri perkayuan di masa yang akan datang.